miR-34a-Mediated Survivin Inhibition Improves the Antitumor Activity of Selinexor in Triple-Negative Breast Cancer - Silvia Martini; Valentina Zuco; Monica Tortoreto; Stefano Percio; Elisa Campi; Rihan El Bezawy; Valentina Doldi; Yosef Landesman; Marzia Pennati; Nadia Zaffaroni (MDPI AG, 2021)
Triple-negative breast cancer (TNBC) is an aggressive disease with limited therapeutic options. Here, we pursued a combinatorial therapeutic approach to enhance the activity of selinexor, the first-in-class XPO1 inhibitor, by miR-34a ectopic expression in human TNBC experimental models. Anti-proliferative activity induced by selinexor and miR-34a expression, singly and in combination, was evaluated by MTS assay and cell counting. The effect of treatments on survivin and apoptosis-related proteins was assessed by western blotting and ELISA. The antitumor and toxic effects of individual and combined treatments were evaluated on TNBC orthotopic xenografts in SCID mice. Selinexor consistently showed anti-proliferative activity, although to a variable extent, in the different TNBC cell lines and caused the impairment of survivin expression and intracellular distribution, accompanied by apoptosis induction. Consistent with in vitro data, the XPO1 inhibitor variably affected the growth of TNBC orthotopic xenografts. miR-34a cooperated with selinexor to reduce survivin expression and improved its anti-proliferative activity in TNBC cells. Most importantly, miR-34a expression markedly enhanced selinexor antitumor activity in the less sensitive TNBC xenograft model, in absence of toxicity. Our data form a solid foundation for promoting the use of a miR-34a-based approach to improve the therapeutic efficacy of selinexor in TNBC patients.